INGGRIS INGGRIS - Cahyo Anggoro; IKE YUNIA PASA IKE; MURHADI MURHADI (Universitas Mercu Buana Yogyakarta, 2025)
This study attempts to create interactive learning media using Articulate Storyline software forIndonesian language lessons in grade IV at Muhammadiyah 1 Elementary School in Purworejo Regency.The development was carried out in accordance with the Design Thinking Method, which consists of fivestages, namely empathize, define, ideate, prototype, and test. This study was motivated by the lowapplication of technology in learning and the need for media that can be used to increase students' interestin learning. Data was collected through observation and interviews with students and teachers. The learningmedia designed combines multimedia in the form of videos, audio, animations, and interactive quizzesbased on Google Forms that are directly connected to Google Spreadsheets for assessment. The media isstored in HTML5 and APK application formats so that it can be accessed via computers or smartphones.The results of the pilot test showed that the learning media developed was categorized as highlyeffective with an average effectiveness score of 4.34 based on the signs of learning interest according toSlameto (2011), which consist of the elements of interest, involvement, enjoyment, and attention. Therefore, this learning media can be used as an alternative solution to improve the quality of interactive Indonesian language learning in elementary schools.